Global ion heating/transport during merging spherical tokamak formation. (16th September 2021) - Tanabe, H.; Tanaka, H.; Cao, Q.; Cai, Y.; Akimitsu, M.; Ahmadi, T.; Cheng, C.Z.; Inomoto, M.; Ono, Y.
Abstract: Here we report global ion heating/transport characteristics of magnetic reconnection during merging spherical tokamak formation experiment on TS-6 (TS-3U). Using the 96CH/320CH ultra high resolution ion Doppler tomography diagnostics, the full- 2 D imaging measurement clearly revealed that magnetic reconnection initially forms localized hot spots in the downstream region of outflow jet with inboard/outboard asymmetry (more deposition in the high field side) but the continuous accumulation of the heating coupled with transport process expands the high temperature region globally and forms characteristic poloidally ring-like structure aligned with field lines. The dynamic ion heating/transport process is also affected by the polarity of toroidal field and poloidally tilted/rotating global structure has experimentally been found both during and after merging. The characteristic poloidal asymmetry gets flipped when toroidal field direction is reversed and it was found that higher temperature appears in the positive potential side, which is opposite to the conventional understanding/prediction of guide field reconnection. Through the parallel acceleration process coupled with global heat transport, poloidally asymmetric non-classical feature has experimentally been found for the first time.